Analyzing the Visual Elements of Title Pages of Persian Lithographed Books Published by Munshi Nawal Kishore (Base on the Collection of the National Library in Iran) - Ali Boozari (نگره, 2022)
Munshi Nawal Kishore (1836-1895) was an Indian journalist, translator, scholar and publisher who, by publishing original and translated books in Persian, had an indisputable role in the promotion of Persian language and literature beyond the borders of Iran, especially in the Indian subcontinent. Many Persian books for the first time, and last time, have been published in India, in Nawal Kishore Publishing house. For about forty years Munshi Nawal Kishore was among the modernist and progressive publishers in India. The books of his publishing house had high literary value and helped to the expansion and excellence of knowledge and insight among the inhabitants of the Indian peninsula. Moreover, publishing hundreds of Persian books – some of which never republished in other Persian-speaking countries like Iran – and exporting them to these countries, helped to the expansion of Persian language and literature in Persian-speaking countries.Moreover, Nawal Kishore publishing house was a leading publisher in terms of book design and introduced a new style for the title pages of its books. Here, the cooperation between gilders and scribes (then “designers”) lead to eye-catching introduction pages for readers. The interesting point about these books is the unique embellishments and spectacular aesthetic structure of their title pages, which distinct them from other lithographed books. From its early days, this publishing house designed a special structure for the title pages of its books to present the book information, including the title, writer, publisher, publication date and place of publishing. This structure becomes a standard for the later Indian books.The purpose of the present study is focusing on the design of title pages in Persian books of Munshi Nawal Kishore Press, to investigate the contribution of these publications in book design in India. The statistical population of this research is 200 titles of Persian books, published between the years 1282-1326 AH. / 1865-1909 and now exist in the collection of National Library of Iran. These books are subject-free and their only feature is that they are visually examined and researched.This research seeks to answer the question that: what were the visual features of the title page that exists in the Persian lithographed books of Munshi Nawal Kishore Press? and this publication is in such a way that it has been obtained to build other systems of medical science books on the page. In this research, it is organized in three parts; after mentioning the background and research method, it is published in Munshi Nawal Kishore and then its feature is introduced visually and described in various sections. To clarify the issue, in some cases, examples of lithography in Iran have been provided. Moreover, to organize this study which is qualitative in terms of its data, and practical in terms of its goal, various sources like books, articles, archives, databases, and various tools such as observation and imaging and studying documents and library research have been used.The results of the study are presented in three sections: visual structure (praising God, book title, writer, publication date, place of publication, publisher), the way the book information is presented, and the embellishments. The innovations of these publications can be classified as follows:Dividing the title pages and assigning each section to one of the information in the book, including the remembrance of God, the title of the book, the name of the author, the date of publication, the place of publication and the publisher.Use of a range of abstract to figurative (plant) ornaments in the design of title pages.Use of poetic and humorous expressions that often contain words leading to circular letters. In this case, not only the audience enjoys reading the poetic phrases, but also visually sees the rhythm and order created by the scribe by repeating the circular letters.Other publishers of the subcontinent embodied the design of title pages because of the public acceptance of this visual and linguistic initiative, and this design method, founded by Newcastle Publications, became a model for designing title pages in Indian books. It should be noted that this special method was invented by Munshi Newelshour Publications and later by Indian publishers of Persian publications.This research reveals that Nawal Kishore publishing house has used various visual elements in the form of recursive embellishments around the pages.